Some examples from a corpus investigation of potentially confusing polysemy and false friends in the terminology of music, centred on English and French, with equivalents in five other languages - Granado, Paola (Array, 2019)
This paper presents five of the initial items of a semantic study of confusable terms and false friends present in the lexis of music in English and French. All forms are also given in Italian, German, Spanish, Russian and Chinese. The object of study is a series of texts from corpora provided by New Sketch Engine, a product of Lexical Computing Limited. In the commentary section, the semantic variance between the different items within the same topic is studied. The approach is essentially synchronic, with priority being given to the examination of current usage. Diachronic considerations are also included where it has been possible to explain, or at least hypothesize how the meaning of the various terms has evolved. The main practical application of the paper is to provide a tool for reducing ambiguity in the area of music terminology. It will be of potential interest to all those concerned by the study and practice of music and the language of music in countries where the languages referred to in this study are in use.